2000
DOI: 10.1093/oxfordjournals.jbchem.a022841
|View full text |Cite
|
Sign up to set email alerts
|

Profile of a Nonylphenol-Degrading Microflora and Its Potential for Bioremedial Applications

Abstract: Nonylphenol (NP) is an important intermediate in the production of various commercial and industrial materials, but is also known as a ubiquitous pollutant in urban aquatic environments. We recently studied the NP-degrading activities of microflora in several aquatic environments, and found a notable degrading activity for wastewater from a sewage treatment plant in Tokyo. This result led us to isolate NP-degrading microbes and identify biodegradation products. Using conventional plate culture techniques and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
36
1

Year Published

2001
2001
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(39 citation statements)
references
References 17 publications
2
36
1
Order By: Relevance
“…In contrast to the NP-degrading isolates of Tanghe et al 30) and Fujii et al 6) , our isolate showed no significant growth and degraded NP in a chemically defined medium with NP as the sole energy and carbon source. We also present gas chromatography-mass spectrometric data concerning the initial attack on the NP molecule by our isolate.…”
contrasting
confidence: 96%
See 2 more Smart Citations
“…In contrast to the NP-degrading isolates of Tanghe et al 30) and Fujii et al 6) , our isolate showed no significant growth and degraded NP in a chemically defined medium with NP as the sole energy and carbon source. We also present gas chromatography-mass spectrometric data concerning the initial attack on the NP molecule by our isolate.…”
contrasting
confidence: 96%
“…In addition, strain YT seems to be more sensitive to NP than strain TTNP3 and S. cloacae JCM 10874. The batch cultures of strain TTNP3 30) and S. cloacae JCM 10874 6) were grown with 600 to 1,000 ppm of NP. In the case of strain YT, the suppressive effect of NP, affecting the lag-phase and the mmax, was found at 100 ppm of NP (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All other chemicals used were of reagent grade. S. cloacae (Fuji et al, 2000) was purchased from Japan Collection of Microorganisms, Riken Bioresource Center (Saitama, Japan); catalog number 10874. The stock cultures were stored at 4 °C in nutrient agar.…”
Section: Methodsmentioning
confidence: 99%
“…Although nonylphenol is recalcitrant in nature, its bioavailability has triggered extensive studies on its bio-remediation by use of some yeast and gram-negative bacteria. Candida aquaetexotoris was reported to decompose the alkyl chain of nonylphenol to give 4-acetylphenol (Vallini et al, 2001), while several bacteria such as Sphingomonas xenophaga (Gabriel et al, 2005), Sphingomonas cloacae (Fuji et al, 2000), and Sphingobium amiense (Ushiba et al, 2003) metabolized its aromatic moiety to the corresponding C9 alcohols.…”
Section: Introductionmentioning
confidence: 99%